Towards an Efficient Resource Allocation based on Software-Defined Networking approach. (June 2021) - Al-Harbi, Adel; Bahnasse, Ayoub; Louhab, Fatima Ezzahraa; Talea, Mohamed
Abstract: Quality of Service (QoS) provisioning in a converged network is a particularly difficult and yet extremely important task. With the coexistence of different types of services, it is challenging to manage and guarantee a good level of performance through manual customization of QoS policies. The Software-Defined Networking (SDN) paradigm can manage the QoS policies and network resources in an automatic and dynamic way through a controller. SDN orchestrates the equipment that supports the OpenFlow protocol. The Hybrid SDN approach provides the ability to manage SDN and legacy equipment. This paper introduces a new intelligent and flexible QoS management model based on the principle of SDN called "Efficient Resource Allocation" (ERA). Experiment comparisons between different QoS mechanisms demonstrate the effectiveness of our proposed model by minimizing delay, latency, jitter, and reducing loss rate. Graphical abstract: Highlights: A new model based on the SDN paradigm for efficient QoS Management in a converged network is proposed. The model aims to dynamically and adaptively manage bandwidth allocation. The proposed model can manage Legacy equipment.